2019
DOI: 10.1519/jsc.0000000000002124
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Muscle Activity of Gymnasts During a Handstand on Various Apparatus

Abstract: Gymnasts perform handstands on various apparatus, both in stable and unstable conditions. Such performances require specific muscle activation, which should differ depending on the condition and expertise of the gymnast. Therefore, the aim of the study was to evaluate 1) the difference in electromyography (EMG) between handstands performed on three apparatus (floor, rings and parallel bars); and 2) the difference between young and well-trained adult gymnasts. Ten adult (25 ± 3.94 years) and 15 young (13.9 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Different gymnastic apparatuses led to specific muscle activation. This activation predominantly depended on hand support conditions, which alternated the primary wrist strategy of handstand balance control, and, as a consequence, the activation of other muscles that control balance [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different gymnastic apparatuses led to specific muscle activation. This activation predominantly depended on hand support conditions, which alternated the primary wrist strategy of handstand balance control, and, as a consequence, the activation of other muscles that control balance [20].…”
Section: Resultsmentioning
confidence: 99%
“…Research into postural control and changes occurring in different settings has been carried out for a number of years [4,6,7,26,27,28,29,30,31]. The process of balance control in handstand has been investigated by a number of researchers [16,19,20,21]. However, there is still a scarcity of data on the differences in balance control strategies depending on the type of the surface.…”
Section: Discussionmentioning
confidence: 99%
“…It was noticed that in the case of experienced athletes the "wrist strategy" plays a dominant role in the control strategy [30][31][32]. In addition, Kochanowicz et al [33] observed that the different gymnastic apparatus led to specific muscle activation. This activation predominantly depended on hand support conditions, which alternated the primary wrist strategy of the handstand balance control, and in consequence, the activation of other muscles controlling balance.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were instructed to use their feet only, not to push or pull their legs. The detailed position of the remaining investigated muscle groups (trunk, knee, and hip extensors) was previously described and shown elsewhere ( Kochanowicz et al, 2019 ). In each position, participants performed three 4-s repetitions, with verbal encouragement to maximize their effort.…”
Section: Methodsmentioning
confidence: 99%